Evaluation of the Access to Health in the 2nd Microregion of Health-CE - Silva, Maria Verônica Sales da; Silva, Maria Josefina da; Silva, Lucilane Maria Sales da; Nascimento, Adail Afrânio Marcelino do; Damasceno, Ana Kelve Castro (Saúde e Sociedade, 2012)
The target of this research is to evaluate the indicators of the Regulation Center of the 2nd Microregional of Heath. METHODOLOGY: documental, descriptive and evaluative study, held in the 2nd Microregional of Health - CE, developed in the appointment setting centers of the districts. The object of study envolved 16 professionals linked to the microregional regulation. The gathering of data was made between February and August 2007, in a documental source. In relation to ethic matters, we have submitted this project to the Ethics Committee of UFC. RESULTS: The application of the parameter of covering allowed us to identify that the districts showed a low tax of appointments specialized to the microregional population. Only 2 districts have more than 90% covering, in the other ones, this parameter is below the estimated, showing two districts with 28% of covering and only one with 13% of covering which represented the lowest percentage. The supervision of PPI in the districts is still an incipient activity in terms of controlling actions. We have noticed that the CMC of the districts of the 2 nd microregional have their outnumbered indicators of offering and demands and the municipal managers do not programm enough to meet the population needs. The structured regulation in this microregion does not improve the utilization of reference services in the supra-municipal spaces, according to the necessity criteria of population health.